The Effect of Effleurage Massage Technique on Afterpains Pain In Multipara Pubber Women at BPM Devi Setiati Bekasi City 2024 - Dwi Reza Wahyuni; Aninditya Azis; Syilvi Nuri Hayati (Oshada, 2025)
Postpartum mothers often experience changes both physiologically and psychologically, one of which is a change in the body's reaction due to uterine contractions called afterpains (meruyan/mules-mules) which lasts 2-14 days after delivery which is often experienced by multiparous parities. causes pain that is sometimes severe enough to require analgesics. To determine the effect of the Effleurage Massage Technique on Affterpains pain in multiparous postpartum mothers at BPM Devi Setiati, Bekasi City in 2024. The research method used in this research is quantitative with a pre-experimental research design with a one group pretest – posttest design approach. The sampling technique used purposive sampling with a total of 30 respondents. The results of research using the Wilcoxon statistical test obtained ρ.value= 0.000 < α=0.05, meaning that there is an influence of the Effleurage Massage Technique on afterpains in multiparous postpartum mothers. Based on data analysis, it is known that in the Negative Range between the pre-test and post-test pain levels there is a difference in Mean Rank of 15.5 and Sum of Rank of 465.0, so there is an increase from the pre-test results to the post-test value after being carried out Effleurage Massage Technique.